AB0098 GENE EXPRESSION AND FUNCTIONAL COMPARISON BETWEEN MESENCHYMAL STEM CELLS FROM LATERAL AND MEDIAL CONDYLES OF KNEE OSTEOARTHRITIS PATIENTS. (June 2019) - Rodriguez, Clara Sanjurjo; Baboolal, Thomas; Burska, Agata; Ponchel, Frederique; El-Jawhari, Jehan; Aderinto, Joseph; Wall, Owen; Pandit, Hemant; McGonagle, Dennis; Jones, Elena
Abstract : Background: Osteoarthritis (OA) is the most common degenerative joint disorder, mainly afflicting the weight–bearing joints, and is the leading cause of physical disability worldwide. Despite the identified risk factors, the exact pathogenesis of osteoarthritis remains unclear (1). Formation of mesenchymal stem cells' (MSC) clusters and their aberrant osteogenic differentiation in OA subchondral bone (SB) has been proposed as a key contributor to progression of OA in animal models (2) and in human hip OA (3). MSCs have a crucial role in joint repair but it remains unknown how OA severity affects MSC numbers or characteristics. Knee OA provides a good model to determine this as in knee OA, distribution of damage is usually asymmetrical and tends to be more severe in the medial (Med) compared to the lateral (Lat) compartment (4). Objectives: The aim of this study was to determine whether there were differences in MSC numbers, topography and gene expression (GE) between Med and Lat femoral condyles of patients with knee OA. Methods: Condyles were obtained from OA patients that underwent total knee replacement (n=16; UK Ethics Committee approval, 14/YH/0087). Decalcified samples were histologically evaluated for cartilage damage, bone sclerosis and CD271+ MSC distribution (2). MSCs were extracted from SB and sorted using the CD271+CD45- phenotype for GE analysis. Colony forming unit (CFU-F) (3), trilineage differentiation (5) and population doubling (PD) assays were performed. MSC numbers, topography and GE were compared between condyles. Results: Med condyles presented significantly higher (p<0.05) degree of cartilage damage (median OARSI score 20, range 15-20) compared to Lat condyles (score 3, range 1.5-15), and sclerotic SB area was higher in the Med condyles (64.3±7.0 vs 27.6±7.4%, p<0.05). CD271+ MSCs were found in bone-lining and perivascular locations, and accumulated in the areas of vascular invasion into the articular cartilage in both, Med and Lat condyles. No differences in the MSC numbers were found using CFU-F assay (1.4±0.7 and 1.6±0.8% of total cells in Lat and Med condyles, respectively), or by flow cytometry (4.4±3.9 and 5.9±6.8%, respectively). MSCs had similar PD and trilineage capacities in vitro . Out of 95 gene tested, 3 genes were significantly upregulated in Med condyle CD271+ MSCs: GREM1 (lateral MSCs below detection), PTHLH (2.4-fold, p=0.02) and STMN2 (10.5-fold, p=0.02), all implicated in osteogenic differentiation and mineralisation (6, 7, 8). Conclusion: Upregulation of ossification-related genes in Med condyle MSCs suggest their potential contribution to sclerotic plate formation and OA severity. Further work is needed to establish if biomechanical or biological stimulation of these MSCs can result in GE modulation in preference of cartilage tissue formation and subchondral bone restoration. References: [1] Conaghan. Nat Rev Rheumatol (2013). [2] Zhen. Nat Med (2013); [3] Campbell. Arthritis Rheumatol (2016); [4] Bae. Cartilage (2010). [5] Altaie. Cytotherapy (2018); [6] Hu. Mol Med Rep (2017); [7] García-Martín. Mol Endocrinol (2014); [8] Chiellini. Biochem Biophys Res Commun (2008) Acknowledgement: CSR funded by fellowship Xunta de Galicia (Consell de Cul, Educ e Ordenación Univ). TB and DM part-supported by NIHR Leeds Musculoskeletal Biomed Research Centre. TB part-supported by FOREUM. JE part-funded by AO foundation start-up grant. Disclosure of Interests: Clara Sanjurjo Rodriguez: None declared, Thomas Baboolal: None declared, Agata Burska: None declared, Frederique Ponchel: None declared, Jehan El-Jawhari: None declared, Joseph Aderinto: None declared, Owen Wall: None declared, Hemant Pandit Grant/research support from: GSK, Consultant for: For education for Bristol Myers Squibb, Dennis McGonagle Consultant for: Lilly, Novartis UCB, Speakers bureau: Lilly, Novartis UCB, Elena Jones: None declared